Internet Gaming Addıctıon, Personality And Quality Of Life Among Young Adults' - Mrs. Sandhya Bhatt, Ms. Kopal Srivastava (International Journal of Advanced Science and Technology, 2020)
In the recent few years, there has been a tremendous increase in the number of people using Internet. Amongst the various engagements available online, gaming is one platform that is widely used and extensively popular, especially among youth. If one reviews the research conducted in the area of internet gaming, one realizes that a large fraction of population from all age groups religiously plays online games and devotes much time, money and effort on it, while overlooking other important aspects of life such as study, work, relationships and personal hygiene. This study  was conducted to study the correlation between internet gaming,  personality factors on quality of life. For this purpose, 60 people (30 boys and 30 girls) who play online games falling within the age range of 17-24 years were sampled from a university setting. For assessing the extent of Internet gaming, the Internet Gaming Disorder Scale-Short Form (IGDS9-SF) was utilized and for assessing quality of life and personality, the WHO Quality of Life-BREF (WHOQOL-BREF) and Big five personality test were used, respectively. The results indicated significant differences in the quality of life, psychological and  social relationships, physical health and environment. On the basis of results it can be said that the Internet gaming indeed influences an individual’s wellbeing by affecting his quality of life and personality.